2017
DOI: 10.1177/1538574417702773
|View full text |Cite
|
Sign up to set email alerts
|

Management of Isolated Atherosclerotic Stenosis of the Common Femoral Artery: A Review of the Literature

Abstract: There is limited data to support endovascular treatment of isolated CFA atherosclerosis. CFE has durable results, but there is significant morbidity and mortality resulting from this procedure. Endovascular interventions have low rates of complications, high rates of technical success, good short-term patency but increased need for repeat interventions when compared to surgery. Further trial data comparing CFE with endovascular therapy is needed to guide the management of CFA stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…More than 50 per cent of patients with PAD undergoing CFE require concomitant endovascular intervention (hybrid procedures) to diseased ipsilateral arteries. Two reviews previously concluded that endovascular interventions to CFA can be performed safely with a high rate of technical success. Since then, two RCTs and two case series on endovascular CFA treatment have been published.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50 per cent of patients with PAD undergoing CFE require concomitant endovascular intervention (hybrid procedures) to diseased ipsilateral arteries. Two reviews previously concluded that endovascular interventions to CFA can be performed safely with a high rate of technical success. Since then, two RCTs and two case series on endovascular CFA treatment have been published.…”
Section: Introductionmentioning
confidence: 99%
“…However, the patient cohort was limited in both studies, and our operation time was similar. Endovascular therapy of the common femoral artery promises a low early mortality compared to surgical treatments (12). A database analysis including over 1000 patients who were treated by endovascular means showed a mortality of 1.6% within the first 30 days (16).…”
Section: Discussionmentioning
confidence: 99%
“…These findings correlated with other operative or endovascular treatments for peripheral arterial occlusion disease 22 . Patency rates for endovascular treatment of the common femoral artery are still sobering; 73% after 1 year are reported for primary patency 12,23 . Bath and Avgerinos 11 described a higher primary patency for routine stenting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a tremendous advancement of procedural success of endovascular therapy, some experts might consider hybrid therapy with endovascular therapy and bypass surgery for complex lesions. In cases of common femoral artery disease involvement, hybrid therapy consisting of endovascular therapy and endarterectomy can be considered although percutaneous common femoral angioplasty might be technically feasible and durable in the short term [ 38 41 ].…”
Section: Practical Endovascular Strategiesmentioning
confidence: 99%